Job quality between institutional differences and convergence - Hauff, Sven; Kirchner, Stefan (Industrielle Beziehungen - Zeitschrift für Arbeit, Organisation und Management, 2014)
The alignment of workplace situation and work values is an important indicator of job quality. From an international comparative perspective, it can be assumed that countries differ regarding the respective mismatch levels owing to institutional differences. However, these differences may be dynamic, and globalization approaches posit a general trend towards convergence. This paper tests these assumptions by asking how countries differ in their mismatch levels and how these differences develop over time. The empirical analysis is based on employee data from 1989 and 2005 for the USA, Great Britain, West Germany, Norway, and Hungary. Findings show that in 1989, West Germany exhibited lower mismatch levels than the USA and Great Britain. In contrast, findings for Norway are mixed, while Hungary displays mostly higher mismatch levels. A partial convergence of job security and income mismatch levels has taken place between the USA, Great Britain, and West Germany. Moreover, our findings underline the persistence of institutional differences in job quality.
CRIS-Team Scopus Importer:2025-04-09
Keywords: Change; Cross-national differences; Employment regime theory; Job quality; Mismatch; Varieties of capitalism; Work values; Workplace situation